2021
DOI: 10.1109/access.2021.3092074
|View full text |Cite
|
Sign up to set email alerts
|

Highly Accurate Prediction Model for Daily Runoff in Semi-Arid Basin Exploiting Metaheuristic Learning Algorithms

Abstract: Developing trustworthy rainfall-runoff (R-R) models can offer serviceable information for planning and managing water resources. Use of artificial neural network (ANN) in adopting such models and predicting changes in runoff has become popular among many hydrologists from a long time. However, since the optimization is the most significant phase in ANN training, researchers' attentiveness has been attracted to the ANN's biggest problem, i.e. its susceptibility of being blocked in local minima. Consequently, us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…The calibration demonstrated a close agreement between observed and computed flows, while the validation yielded satisfactory results (Haddad 2022). Aoulmi et al (2021) present a new prediction model for rainfall-runoff in a semiarid basin. The model, called ANN-IPSO, combines an artificial neural network with an improved particle swarm optimization algorithm.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…The calibration demonstrated a close agreement between observed and computed flows, while the validation yielded satisfactory results (Haddad 2022). Aoulmi et al (2021) present a new prediction model for rainfall-runoff in a semiarid basin. The model, called ANN-IPSO, combines an artificial neural network with an improved particle swarm optimization algorithm.…”
Section: Introductionmentioning
confidence: 78%
“…The study concludes that the ANN-IPSO algorithm is superior in terms of statistical criteria and graphical interpretation when using input predictors Rt, Rt−1, and Qt−1. (Aoulmi, Marouf ,et al 2021). Gebre Gelet ( 2023) presents a study that evaluated the performance of three models (SWAT, HBV, and HEC-HMS)( Soil and Water Assessment Tool, Hydrologiska Byråns Vattenbalansavdelning, Hydrologic Engineering Center-Hydrologic Modelling System) for rainfall-runoff simulation in the Katar catchment in Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…This year, Bell Grand predicted the flood three days ago using the telegraph and the very simple relationship between rising levels in the tributaries and rising levels of the Seine River in Paris (Berz, 2000). This prediction led to a reduction in casualties and financial losses (Aoulmi, 2021). Since then, we have seen tremendous progress in the field of communication systems and flood forecasting and warning systems.…”
Section: Introductionmentioning
confidence: 99%
“…The objective of training the MLP is to adjust the connection weights and biases to teach the neural network how to estimate different inputs and generate desired outputs(Mai et al 2022). Previous research has shown the effectiveness of metaheuristic algorithms in optimizing MLP networks(Zhou et al 2020;Aoulmi et al 2021;Jafari-Asl et al 2021;Liu et al 2021). These algorithms are commonly employed for training because they can efficiently identify the best overall solution.…”
mentioning
confidence: 99%